Effectiveness of 2024 Hypertension Guidelines Implementation in Improving Hypertension Control - Deslina, Deslina; Martha, Evi (Poltekkes Kemenkes Jakarta III, 2025)
The implementation of hypertension guidelines is crucial for controlling hypertension and reducing its complications. This study aims to evaluate the implementation of the 2024 hypertension guidelines at Puskesmas X in terms of the percentage of controlled, uncontrolled, and Missed Visits in hypertensive patients. Data were collected from the hypertension control program records at Puskesmas X, obtained through the community health center's information system, for four months before and four months after the new guidelines were implemented. This study employed a retrospective quantitative design with a comparative approach, using an independent t-test to determine statistical significance. The statistical results showed a significant increase in the percentage of controlled hypertension after the implementation of the guidelines (p < 0.05), while uncontrolled hypertension and Missed Visits did not show significant changes. These findings provide an initial evaluation of the effectiveness of the new guidelines in improving hypertension control and highlight the need for additional interventions to improve patient adherence to follow-up visits.